Study of the links between organizational culture and quality of educational services in the institutional image of a private confessional university - Turpo Chaparro, Josué (2017)
The quality of academic services, along with the institutional image and organizational culture are key factors in the university licensing process. This study explores the relationship between the quality of academic services and the organizational culture in the institutional image of a private denominational institution. It's a correlational research and used a quantitative approach. It is a multiple purpose causal correlation that seeks to explain existing relationships, through multiple linear regression analysis ANOVA. Three instruments were applied: Denison's 60-item Organizational Culture Survey (DOCS); The Student Satisfaction Scale Instrument for Educational Quality (SEICE) of 93 items and the Escobar's Institutional Image questionnaire for selected audiences of 31 items. The culture andquality instruments used as an evaluation the Likert scale of five points, in the case of the image instrument through positive and negative signs was scored. The instruments were applied to a population of 221 people of the public students of a confessional private university. Among the results, significant relationships were obtained between the studied variables and their dimensions. We conclude that the positive evaluation of the institutional image is affected by the organizational culture and the quality of educational services.